Adaptation of Wetland Farming Communities to Modernization: Case Study in Jelapat 1 Village, Indonesia - Ruswinarsih, Sigit; P, Reski; Norkamaliah, Norkamaliah; Situmorang , Tesaleonika (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2024)
Modernization can bring progress on the one hand, but on the other hand, modernization may not provide the expected benefits, such as increasing dependence on expensive agricultural inputs and climate change which has an impact on agricultural practices. The main theme of the research is wetland farming communities facing the flow of modernization to outline farming community strategies in adapting wetland farming practices. This research uses a qualitative approach with a case study method based on considering the specificity of the theme according to the characteristics of the research area in Jelapat 1 Village, Tamban District, Barito Kuala Regency. Informants were selected purposively using the criteria of character, membership of farmer groups, and willingness to become informants. Data was collected using observation methods, in-depth interviews, and documentation to obtain valid and varied data. Data were analyzed through data reduction, data presentation, and conclusion drawing stages. For data credibility, triangulation techniques were used. The research results show that farmers in Jelapat 1 Village face water conditions that always inundate agricultural land, which is difficult to control due to strong natural factors. The challenges faced by farmers besides pasang pandit are also dwarf pests and birds. Concerning modernization, it can be concluded that farmers in Jelapat 1 Village use traditional knowledge in adapting agricultural practices in wetlands, namely, arranging planting patterns, making simple water channels, selecting superior seeds that suit wetland criteria, and using organic fertilizer. This phenomenon indicates the conservation of local wisdom in wetland farming in Jelapat 1 Village by the farming community.